Value and risks of morphing technology into strategy and business model - A. L. Denisova; A. N. Lopatnikov (Управление)
Digital technologies became the primary source of innovation in the private and public sectors. The Internet profoundly changed the way businesses are run catapulting “most digital” industries and companies to the top of the S&P500. Two innovations that drive digital transformation changing the nature of competition are cloud computing and artificial intelligence (AI) technologies. Cloud-native business models and strategies proved successful in various industries, while AI is being tested in vivo by management mainstream. The publication provides an analysis of a multidimensional impact cloud computing makes on strategies and business models of companies. We show that what made cloud computing special in the management context was the way it morphed into strategies and business models best suited for the uncertain future. We also noted that as the focus of digital transformation shifts towards cloud-based AI powered decision-making solutions, managing the human aspect of “more digital” business models and related risks, recently referred to as an existential threat, becomes a priority of management research.